From Scientism to Humanism - the Influence of Modern Western Cultural and Ideological Thoughts on Lu Xun - Chenlin, Wei (Advances in Social Sciences Research Journal, 2020)
Lu Xun’s shift from “saving the nation through science” to “saving the nation through literature” was an important watershed in modern China’s process of learning from the West, as well as in Lu Xun’s personal transition from Scientism to Humanism. As interpenetrating and intertwining aspects of modern Western culture, Scientism and Humanism are at the same time mutually different and mutually interrelated. In the past, most researchers have focused on the differences between these two cultural thoughts and neglected their connections. But actually, precisely because they are connected and interrelated to each other, Lu Xun actively kept up with the latest philosophical and cultural trends in the West at the same time he was introducing the scientific achievements of the West; this is also why Lu Xun first taught science after returning to China, then switched to teaching literature after the May Fourth Movement.He also urged people who were engaged in literature to also read scientific books. Only by realizing the differences between the two and paying attention to their connections can we better understand Lu Xun’s cultural choice between Scientism and Humanism.